Characteristics and Factors Related to Eyelid Basal Cell Carcinoma in Saudi Arabia - Al Wohaib, Manar (Middle East Afr J Ophthalmol, 2018)
PURPOSE: Data on basal cell carcinoma (BCC) from the Middle East are deficient. We present the features and management outcomes for BCC over the last 36 years in Saudi Arabia. SUBJECTS AND METHODS: This retrospective chart review included BCC patients diagnosed and treated at Saudi Arabia between 1980 and 2016. Data were collected on patient demographics, clinical and histopathological characteristics of the lesions, management, and follow-up. RESULTS: One hundred and twenty-six patients with BCC were included in this study. The incidence of BCC in Saudi Arabia is 0.8 cases a year. The median age of the patients was 71 years. BCC affected 58.9% of males. The lower lid was the most common site of occurrence (52.7%). Clinically, BCC was most commonly recognized as a mixed lesion (41.1%) and 50.4% were histologically nodular. Risk factors for poor prognosis included tumor localization in the medial aspect of the lid, tumor size > 5 mm, histological subtype being ulcerative or morphea forms, affected margins, and recurrent lesions. CONCLUSION: BCC is a rare condition in Saudi Arabia. The clinical features and histopathology of BCC in Saudi Arabia are similar to the patterns observed in other regions of the world. Early detection and timely management mitigates the extensive destructive ocular/orbital damage due to BCC and results in better patient outcomes.